James Fowler Simmons papers - Simmons, James Fowler, 1795-1864.
Correspondence, memoranda, business and legal records, account books, printed matter, photographs, and other papers relating to Simmons's cotton and yarn manufacturing enterprises, Rhode Island and national politics, and economic and social conditions in Rhode Island. Subjects include the Bank of the United States, bounty laws, Thomas Wilson Dorr and the Dorr Rebellion of 1842, exporting and importing, William Henry Harrison, Abraham Lincoln, manufacturing, James K. Polk, the Whig Party, slavery, tariff, and the annexation of Texas. Includes correspondence with Simmons's son, Walter C. Simmons and other family members. Other correspondents include Lawrence F. Abbott, Charles Francis Adams, Henry B. Anthony, Hervey Armington, Zenas R. Bliss, Leslie Combs, H.G. Cranston, Robert Bennie Cranston, Asbury Dickins, Edward J. Eno, Edward Everett, William Ferguson, Elbridge Gerry, William C. Gibbs, William Hunter, Charles Jackson, George W. Jackson, Thomas A. Jenckes, Nehemiah Rice Knight, Abraham Lincoln, Samuel Finley Breese Morse, Charles Potter, Richard K. Randolph, Nathan S. Ruggles, Nathan Sargent, William Henry Seward, Nathaniel Pitcher Tallmadge, Joseph L. Tillinghast, John Tyler, Amasa Walker, William A. Watson, and Daniel Webster; and the firms, Abbott & Bliss, Fearing & Hall, Liverman & Cushing, and Tiffiny, Ward & Co.
Microfilm edition of selected correspondence available
Photocopies produced from correspondence available on Microfilm 6,358 in the Manuscript Division.
Manufacturer, political leader, and U.S. senator from Rhode Island.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbott, Lawrence F. -- 1859-1933 -- Correspondence; Adams, Charles Francis, -- 1807-1886 -- Correspondence; Anthony, Henry B. -- 1815-1884 -- Correspondence; Armington, Hervey -- 1793-1868 -- Correspondence; Bliss, Zenas R. -- 1835-1900 -- Correspondence; Combs, Leslie, -- 1793-1881 -- Correspondence; Cranston, H. G. -- Correspondence; Cranston, Robert Bennie, -- 1791-1873 -- Correspondence; Dickins, Asbury, -- 1780-1861 -- Correspondence; Dorr, Thomas Wilson, -- 1805-1854.; Eno, Edward J. -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Ferguson, William -- Correspondence; Gerry, Elbridge, -- 1791-1883 -- Correspondence; Gibbs, William C. -- 1789-1871 -- Correspondence; Harrison, William Henry, -- 1773-1841.; Hunter, William, -- 1774-1849 -- Correspondence; Jackson, Charles, -- 1775-1855 -- Correspondence; Jackson, George W., -- 1803 or 1804-1860 -- Correspondence; Jenckes, Thomas A. -- 1818-1875 -- Correspondence; Knight, Nehemiah Rice, -- 1780-1854 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Morse, Samuel Finley Breese, -- 1791-1872 -- Correspondence; Polk, James K. -- 1795-1849.; Potter, Charles -- Correspondence; Randolph, Richard K. -- 1781-1849 -- Correspondence; Ruggles, Nathan S. -- Correspondence; Sargent, Nathan, -- 1794-1875 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Simmons, Walter C. -- Correspondence; Tallmadge, Nathaniel Pitcher, -- 1795-1864 -- Correspondence; Tillinghast, Joseph L. -- 1791-1844 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Walker, Amasa, -- 1799-1875 -- Correspondence; Watson, William A. -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Simmons family -- Correspondence; Abbott & Bliss -- Correspondence; Bank of the United States (1816-1836); Fearing & Hall -- Correspondence; Liverman & Cushing -- Correspondence; Tiffany, Ward & Company -- Correspondence; Whig Party (U.S.); Bounties -- United States; Cotton manufacture -- Rhode Island; Dorr Rebellion, 1842.; Elections -- United States -- 1860.; International trade; Manufacturing industries -- United States; Presidents -- United States -- Election -- 1860.; Slavery -- United States; Tariff -- United States; Textile industry -- Rhode Island; Yarn; Rhode Island -- Economic conditions; Rhode Island -- History -- 1775-1865.; Rhode Island -- Politics and government; Rhode Island -- Social conditions; Texas -- Annexation to the United States